Evolution of theoretical ecology in last decades: why did individual-based modelling emerge - Uchmański, Janusz; Kowalczyk, Kamila; Ogrodowczyk, Piotr (Ecological Questions, 2008)
Mathematical models of classical theoretical ecology are state variable models. They use density of population as a state variable. Because such models posses equilibrium states and they are stable around them, classical theoretical ecology has been dominated by considerations about stability of ecological systems. Three factors observed in ecology in last decades had great influence on the gradual decline of the classical theoretical ecology: first one is development of evolutionary ecology and the stress it laid on individuals, the second one nonequlibrium way of thinking about dynamics of ecological systems and the third one various methodological doubts about application of difference and differential equations in ecology. Individual-based modeling has emerged as the result of this discussions. However, individual-based approach to modeling the dynamics of ecological systems has natural tendency to describe particular systems and to produce their detailed models. Much should be done in the future to solve general problems formulated by classical theoretical ecology using method of individual-based approach.